Integrative Analysis of the Transcriptome and Metabolome Reveals Genes Involved in Phenylpropanoid and Flavonoid Biosynthesis in the Trapa bispinosa Roxb. - Yin, Dong-Jie; Ye, Shi-Jie; Sun, Xiao-Yan; Chen, Qin-Yi; Min, Ting; Wang, Hong-Xun; Wang, Li-Mei (Frontiers in Plant Science, 2022)
Background: Trapa bispinosa Roxb. is widely grown worldwide as an important aquatic cash crop. Current research on Trapa bispinosa is primarily focused on the separation and identification of active ingredients, as well the inhibitory effect on tumors, making research on the molecular mechanism of secondary metabolite accumulation relatively weak. As such, an integrative analysis of transcriptome and metabolome is required to identify the key metabolic pathways, key genes, and explain the molecular mechanism of Trapa bispinosa. Results: The biosynthesis pathways of phenolics in Trapa bispinosa were investigated through transcriptome and metabolome analyses. Transcriptome analysis yielded 42.76 million clean reads representing 81,417 unigenes with an average length of 1,752 bp. According to KEGG pathway analysis, 1623 unigenes, including 88 candidate unigenes related to phenolics biosynthesis, were up-regulated in water chestnut shell (FR) when compared to leaves (LF), root (RT), and stem (ST). The FR vs LF group had the highest number of specific genes involved in phenylpropanoid, flavonoid, flavone, and flavonol biosynthesis pathways of all comparison groups. In addition, RNA sequencing revealed 18,709 SSRs spread across 14,820 unigenes and 4,387 unigenes for encoded transcription factors. Metabolome analysis identified 793 metabolites, which included 136 flavonoids and 31 phenylpropane compounds. There were 202 differentially accumulated metabolites (DAMs) in the FR vs LF group. The combined transcriptome and metabolome analyses revealed a significant correlation of 1050 differential expression genes (DEGs) with 62 DAMs. In this view, a schematic of flavonoid biosynthesis was proposed in the FR vs LF group, providing evidence for the differences in genes and metabolites between FR and LF. Conclusion: This study, through de novo transcriptome assembly and metabolome analysis, identified several DEGs and DAMs, which were then used to build flavonoid biosynthesis pathways and a correlation network. The findings lay the groundwork for future research into the molecular mechanisms and functional characterization of Trapa bispinosa candidate genes for phenolics biosynthesis.